Length-weight Relationship, Condition Factor and DNA Barcoding of Bonylip Barb, Osteochilus vittatus (Valenciennes, 1842) in Dampelas Lake, Central Sulawesi, Indonesia - Serdiati, Novalina; Ndobe, Samliok; Rosyida, Eka; Gani, Abdul; Hermawan, Roni; Nurdin, Muh. Saleh; Sari, Devi Elvina; Herlina, Sri; Pawaro, Moh. Fadlan Daeng; Danty, Astri Rahma (Journal Omni-Akuatika, 2024)
Dampelas Lake, also known as Talaga Lake, in Central Sulawesi Indonesia, lacks data on fish communities, especially biological aspects, including a wild population of bonylip barb Osteochilus vittatus (Valenciennes, 1842). Locally known as ikan nilem, this freshwater fish commodity is not native to Sulawesi. The purpose of this research was to analyze the length-weight relationship, condition factor and DNA barcode of the bonylip barb population in Dampelas Lake. Bonylip barb specimens (101 males and 78 females) were collected from Lake Dampelas during July 2023 using fish traps. The total length and weight ranges were 57-211 mm and 3-107 g. Length-weight relationships were W = 3×10-5 L2,8219 (males); W = 3×10-6 L3,2574 (females); and W = 1,1×10-5 L3,0176 (both sexes combined), indicating an isometric growth pattern. Condition factor ranged from 0.471-1.652 with similar mean values for males (1.01) and females (1.02). DNA barcodes for Lake Dampelas bonylip barbs nested in one of four O. vittatus clades, indicating a need for reviewing Osteochilus taxonomy. Most adult females had spent gonads, indicating seasonal spawning, with implications for developing an economically viable fishery which could also help control this non-native species in Dampelas Lake.Keywords: Cyprinidae, freshwater fisheries, growth pattern, introduced fish, mitochondrial DNA